Olivocochlear efferent function: issues regarding methods and the interpretation of results - Guinan Jr., John J. (Frontiers in Systems Neuroscience, 2014)
As studies of the olivocochlear (OC) efferent system have matured, issues have been identified that need to be taken into account in the design of new studies and in the interpretation of existing work. The need for high signal-to-noise ratios (SNRs), multiple alternations of conditions, and avoiding middle-ear-muscle activation have been previously highlighted. Less well-known issues include: Contralateral medial OC (MOC) effects may not be good proxies for ipsilateral MOC effects; MOC-induced changes in otoacoustic emissions (OAEs) may not accurately show MOC-induced changes in auditory-nerve responses; Measuring OAE differences from before to after psychophysical trials yields the transient OAE change but not tonic MOC activation; Tonic MOC activation may be measurable by several techniques including by OAE differences in trials in which the subject’s judgment was correct versus trials that were incorrect; SNRs can be preserved by Bootstrap statistical tests; Differences in task difficulty may outweigh differences in subject attention; Lateral efferent effects are little understood and may be tied to MOC effects; To assess whether MOC strength predicts protection from acoustic trauma, prospective tests in humans are needed.